2023
DOI: 10.1002/ajh.26866
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and symptoms among patients with relapsed/refractory AL amyloidosis treated with ixazomib‐dexamethasone versus physician's choice

Abstract: Patient‐reported outcomes in AL amyloidosis have not been well‐studied. We analyzed health‐related quality of life (HRQOL) and AL amyloidosis symptoms data from the phase 3 TOURMALINE‐AL1 trial (NCT01659658) (ixazomib‐dexamethasone, n = 85; physician's choice of chemotherapy [PC], n = 83). HRQOL and symptom burden were measured with the SF‐36v2, Functional Assessment of Cancer Therapy/Gynecologic Oncology Group Neurotoxicity subscale (FACT/GOG‐Ntx), and an amyloidosis symptom questionnaire (ASQ). Score changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Patients treated with ixazomib showed an increased risk of cardiac arrhythmias (26% vs. 15%), but the Authors assessed that the difference was mainly due to the greater frequency of non-drug-related atrial fibrillation (8% vs. 1%) ( 100 ). Although the study did not meet the primary endpoints of hematologic response, further analysis revealed that ixazomib administration is associated with similar or trended better quality of life and symptoms manifestation, compared with control regimens ( 101 ). In a phase I/II study, ixazomib-cyclophosphamide-dexamethasone was safe and well tolerated in patients with a new diagnosis of AL amyloidosis ( 102 ).…”
Section: Cardiovascular Toxicities Of Therapies For Al Amyloidosismentioning
confidence: 93%
“…Patients treated with ixazomib showed an increased risk of cardiac arrhythmias (26% vs. 15%), but the Authors assessed that the difference was mainly due to the greater frequency of non-drug-related atrial fibrillation (8% vs. 1%) ( 100 ). Although the study did not meet the primary endpoints of hematologic response, further analysis revealed that ixazomib administration is associated with similar or trended better quality of life and symptoms manifestation, compared with control regimens ( 101 ). In a phase I/II study, ixazomib-cyclophosphamide-dexamethasone was safe and well tolerated in patients with a new diagnosis of AL amyloidosis ( 102 ).…”
Section: Cardiovascular Toxicities Of Therapies For Al Amyloidosismentioning
confidence: 93%
“…We chose to include the FACT/GOG-Ntx-13 as it holds information on both quality of life and neuropathy. It was not originally developed for haematological cancers, but it has been widely used in other studies within this patient group (155,169,(260)(261)(262). The questionnaire is considered among the best PROs to capture CIPN (166,185,263,264).…”
Section: Test Of Neuropathymentioning
confidence: 99%